The need for the presence, absence or alternation of the null subject in the Spanish language - al-Shammari, Dr. Mowaffaq H. Mansi (Al-Adab Journal, 2021)
In this study we develop a didactic unit, in which we try to determine the cases in which the presence, absence and alternation of the null subject in the Spanish language will be necessary, the purpose of the work will be to support the task of the teacher and the student in the process of teaching Spanish as a second language or as a foreign language.